Ethnobotanical investigations on plants used in folk medicine by native people of Kumaun Himalayan Region of India - Tiwari, Devesh; Sah, Archana N; Bawari, Sweta; Bussmann, Rainer W (Ethnobotany Research and Applications, 2020)
Background:A large population in the rural area of Uttarakhand is still dependent upon traditional plant-based knowledge to combat various disease conditions. This study aimed to explore the ethnopharmacological information and document traditional uses of plants in the Kumaun Himalayan region. Here we show the study of nine villages of three districts of the Uttarakhand state in India, located in the western Himalayan region. Methods:A total of 26 traditional healers and experienced inhabitants between 30-85 years of age were interviewed by a semi-structured questionnaire. The data obtained was quantitatively evaluated using use value (UV). Further, the informant consensus factor (ICF) and fidelity level (FL) were also calculated for species having UV higher than 0.15. Results:A total of 56 plant species were reported from 34 families. The highest number of plant species were collected from Asteraceae and Lamiaceae families followed by Rosaceae. Primary uses of plants were categorized into 29 disease categories. The highest number of species was reported to be used for gastrointestinal disorders (11.21%) followed by immuno-modulation, anti-stress, as adaptogens (10.2%), analgesics (7.47%), for nervous system related disorders (6.54%) and as antimicrobials (6.54%). Conclusions:Local traditional knowledge and practice of plant-based medicine is quite widespread in the rural areas of Uttarakhand and is an indispensable part of the healthcare system. It plays a vital role in the absence of basic medical facilities and tremendous paucity of trained medical personnels. Keywords:Ethnobotany, Himalaya, Cordyceps, Uttarakhand